Development of a multiplex Endopep-MS assay for simultaneous detection of botulinum toxins A, B and E. Issue 1 (December 2017) - Rosen, Osnat; Feldberg, Liron; Yamin, Tamar; Dor, Eyal; Barnea, Ada; Weissberg, Avi; Zichel, Ran
Abstract Botulinum neurotoxins (BoNTs) are bacterial proteins that cause botulism, a life-threatening disease. The Endopep-MS assay permits rapid detection and serotypic differential diagnosis of BoNTs. The serotype-specific nature of this assay requires that each serum sample be aliquoted and individually tested, which in addition to the limited volume of clinical samples, especially in infants, points to the need for a multiplex assay. However, previous attempts to develop such an assay have been challenging, mainly due to inhibition of BoNT/A activity by the BoNT/E peptide substrate. BoNT/A and BoNT/E share the same native target protein as their substrate. We hypothesized that the steric interference between the BoNT/A and BoNT/E substrate peptides is responsible for the difficulty in simultaneously assaying these two toxins. To explore the basis for steric interference, we used the reported structure of BoNT/A in complex with SNAP-25 and modelled the structure of BoNT/E with SNAP-25. Following this thorough structural analysis, we designed a new peptide substrate for BoNT/A that maintained the assay sensitivity and allowed, for the first time, simultaneous detection of the three most abundant human botulinum serotypes. Adopting the multiplex assay will minimize the required sample volume and assay time for botulinum detection while maintaining the superior Endopep-MS assay performance.